Development of Power System Infrastructure Model for the Island Communities: A Case Study of Kokorotan Island in Indonesia - Rumbayan, Meita (IJRDO - Journal of Electrical And Electronics Engineering, 2017)
The purpose of this study is to develop a model of power system infrastructure based on renewable energy available locally in a remote island. This research is a case study for Kokorotan Island that located in eastern Indonesia region of Talaud Island regency of North Sulawesi province in Indonesia. The research methods used are data collection and data analysis using software HOMER. The monthly average daily radiation is 5.62 kWh/m2, while the wind speed ranging from 3 to 5.3 m/s in Kokorotan island. The proposed hybrid power system model consists of a PV component of Canadian Solar Max Power C56x-325P of 150 KW PV, 70 string of Surette 6CS25P, 1 wind turbine of 1.5 kW Pika T701, Diesel Generator 50 kW and converter Magnum MS4448PAE 25 kW. The annual electricity production from the PV Diesel system for Kokorotan island is 312.595 kWh in which 80% electricity comes from renewable energy (PV and Wind energy) as well as 20% electricity comes from diesel. The cost of generating electrical energy in the term of cost of energy (COE), Net Present Cost (NPC) and operating cost are 0.314 US/kWh, 725.086 US and 37.973 US respectively. The cost of generating electrical energy with renewable energy is relatively high then it is necessary to have policies and strategies for the development of power infrastructure for the sake of the energy security of island communities in Indonesia.